Efficient Delivery of Triptolide Plus a miR-30-5p Inhibitor Through the Use of Near Infrared Laser Responsive or CADY Modified MSNs for Efficacy in Rheumatoid Arthritis Therapeutics - Zhang, Xiaonan; Zhang, Xin; Wang, Xipeng; Wang, Tao; Bai, Bin; Zhang, Na; Zhao, Yanjiao; Yu, Yang; Wang, Bing (Frontiers in Bioengineering and Biotechnology, 2020)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease for which treatment focuses on suppressing an overactive immune system and maintaining the physiological balance of synovial fibroblasts (SFs). We found that miR-30-5p was highly expressed in rheumatoid arthritis synovial fibroblasts (RASFs). Subsequently, we predicted that phosphatidylinositol 3-kinase regulatory subunit 2 (PIK3R2) might be a putative target of miR-30-5p. Recent studies have reported that PIK3R2 can maintain the physiological homeostasis of RASFs. Therefore, miR-30-5p inhibitor has the potential to be used in the treatment of RA, but low levels of miR-30-5p inhibitor internalization affect its application. Triptolide (TP) is an effective drug in the treatment of RA but induces severe toxicity and has a narrow therapeutic window. In this study, the cell internalization performance of miR-30-5p inhibitor was improved by loading it into cell membrane penetrating peptide (CADY)-modified mesoporous silica nanoparticles (MSNs), and the toxicity of TP was decreased by loading it into a controlled drug release system based on MSNs. The nanodrug carrier was constructed by filling a phase-change material (PCM) of 1-tetradecanol and drugs into MSNs that could be triggered by an NIR laser with thermo-chemo combination RA therapy. Our results show that the miR-30-5p inhibitor-loaded MSNs@CADY significantly inhibited RASF proliferation and increased apoptosis. In addition, MSNs@PCM@TP under 808 nm laser irradiation were effective in downregulating immune system activation in an RA rat model. Finally, the results of a pharmacodynamics study showed that the combination of MSNs@CADY@miR-30-5p inhibitor and MSNs@PCM@TP under 808 nm laser significantly increased the effectiveness of RA treatment. These findings provide a novel understanding of RA pathogenesis and a theoretical basis for RA treatment.